India-China interface and the road ahead - International Seminar on India-China Interface and the Road Ahead (2008 : Asiatic Society); Ray, Haraprasad, 1931-; Asiatic society (Kolkata) (Kolkata : Asiatic Society, 2012)
Papers presented at the International Seminar on India-China Interface and the Road Ahead, held at Asiatic Society during 28-29 November 2008.
Includes bibliographical references
Keywords: India -- Foreign relations -- China; China -- Foreign relations -- India